1989
DOI: 10.1111/j.1440-6055.1989.tb00894.x
|View full text |Cite
|
Sign up to set email alerts
|

LABORATORY STUDIES ON THE LIFE HISTORY OF NOMADACRZS GUTTULOSA (WALKER) (ORTHOPTERA ACRIDIDAE)

Abstract: The spur-throated locust Nomadacris guttulosa (Walker) was reared under laboratory conditions for the first time. Females were larger and heavier than males and had 1-3 additional instars. Eye stripe number was the most useful indicator of instar number. Male nymphs changed colour from green to brown on average 1 instar earlier than females. Ratios of adult hind femur length/head capsule width and fore wing lengthlhind femur length were independent of sex. The ratios obtained were similar to those expected of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
26
0
2

Year Published

1991
1991
2012
2012

Publication Types

Select...
8

Relationship

4
4

Authors

Journals

citations
Cited by 12 publications
(28 citation statements)
references
References 3 publications
0
26
0
2
Order By: Relevance
“…As mentioned above, the effects of host plants, crowding and humidity on the number of instars have been proved for some insects (Long 1953;Leonard 1968;Ballmer & Pratt 1989;Elder 1989;Penz 1990;Casimero et al 2000;Bentancourt et al 2003Bentancourt et al , 2004Azidah & Sofian-Azirun 2006). In the present study, since the rearing was carried out individually with 65Á75% relative humidity and a single food was used, these responses could not be considered.…”
Section: Effect Of Photoperiod On Number Of Instarsmentioning
confidence: 96%
See 1 more Smart Citation
“…As mentioned above, the effects of host plants, crowding and humidity on the number of instars have been proved for some insects (Long 1953;Leonard 1968;Ballmer & Pratt 1989;Elder 1989;Penz 1990;Casimero et al 2000;Bentancourt et al 2003Bentancourt et al , 2004Azidah & Sofian-Azirun 2006). In the present study, since the rearing was carried out individually with 65Á75% relative humidity and a single food was used, these responses could not be considered.…”
Section: Effect Of Photoperiod On Number Of Instarsmentioning
confidence: 96%
“…The number of instars, however, varies intraspecifically in a considerable number of species. Variation in number of instars has been reported to be related to factors such as sex (Fleischmann et al 1968;Penz 1990;Garcia-Barros 2006;Esperk et al 2007b), temperature (Roberts et al 1978;Tanaka 1979;Kamata & Igarashi 1995;Zhu & Tanaka 2004;Kingsolver 2007), humidity (Elder 1989), photoperiod (Ingram & Jenner 1976;Tanaka 1979;Tanaka et al 1999;Taniguchi & Tomioka 2003;Zhu & Tanaka 2004), crowding (Long 1953;Leonard 1968), host plants or food quality and quantity (Penz 1990;Casimero et al 2000;Bentancourt et al 2004;Azidah & Sofian-Azirum 2006) and heredity (Brehme 1939;Solonon 1973;Zhou & Topp 2000) in many insects.…”
Section: Introductionmentioning
confidence: 99%
“…guttulosa reared from egg in individual glass jars indicated that the species was sexually dimorphic, females being larger than males (Elder 1989).…”
Section: Introductionmentioning
confidence: 99%
“…Under conditions of continuing high moisture, oviposition may be prolonged leading to outbreaks. Elder (1989Elder ( , 1991 studied the life history and effect of environmental factors on sexual maturation of A . guttulosa in the laboratory.…”
Section: Introductionmentioning
confidence: 99%